Amphibian fauna of Kuwait - Indraneil, Das; Aaron M., Bauer (Springer Nature, 2025)
The chapter provides a review of the amphibian fauna of Kuwait. A single amphibian species is known from Kuwait. Originally referred to as Bufo viridis Laurenti, 1768, and more recently as Bufotes variabilis, the Kuwaiti example specimen has been referred to as Bufotes sitibundus (Pallas, 1771).